IDEOLOGI PENDIDIKAN PESANTREN DAN PENGARUHNYA TERHADAP PERILAKU IBADAH SHOLAT SANTRI PONPES KHOZINATUL ULUM BLORA - Partono (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2018)
Islamic boarding schools as the center of tafaqquh fiddin ideology education are expected to have implications for the formation of personal and social piety especially in the form of worship behavior. This paper tries to describe the important role of the education ideology of Khozinatul Ulum Blora Islamic Boarding School by revealing some facts to the extent that the ideology of Islamic boarding school education influences the worship behavior at Khozinatul Ulum Blora Islamic Boarding School. The results of the study show that the ideology of boarding schools is able to make individual beliefs of santri. Individual beliefs and behavior are aligned to some degree, their ownership of those beliefs is strengthened or justified by appropriate behavioral patterns until finally it comes to the conclusion that